Application of TESOL methodology in English lessons as part of a student-oriented approach (Eurasian Research Bulletin, 2023)
With the development of education globalization, the demand for international English teachers with standardized professional teaching skills is more and more urgent. An increase in new methods in recent years indicates the need for such a model. In view of this situation, TESOL curriculum design emphasizes that the focus of language teaching is to use meaningful language in a wide range of contexts, which covers the advantages of the current English teaching methods and makes improvements. TESOL teaching is a teaching method with “students as the subject and teachers as the auxiliary” achieved good results.